Assessment of Smoking Dependence by FAGERSTRŐM Test and its Association with Some Comorbidities and Educational level - Marwah Riyadh Salim,; Hashim Mahdi Hashim,; Dawood, Haider (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Nicotine addiction is the inevitable result for many smokers. Regardless of control and intervention strategies for smoking cessation, it is important to determine the nicotine dependence score for each smoker. Objectives: To assess the nicotine dependence by FAGERSTRŐM Test for nicotine dependence (FTND score) and to find out the association of nicotine dependence with some smoking-related comorbidities and with the level of education.Patients and Methods: This is a cross-sectional study on a total of 200 adult smokers who were attending different departments in Al-Imamain Al-Kadhimain Medical City during the period from April 2019 to October 2019. Demographic data including age, sex and educational level, number of cigarettes/day, number of attempts to quit smoking, as well as comorbidities including hypertension, ischemic heart disease, and malignancies were obtained. Nicotine dependency was assessed by FTND which consists of six items and has a total maximum score of 10. Results: The overall average of FTND among smokers was 5.8 ± 2.81. A low score was found in 12.5% of the participants, moderate score in 33% and high score in 54.5%. FTND score showed a significant positive correlation with the number of cigarette/day (r= 0.758, p< 0.001), age of the smoker (r= 0.457, p